2022
DOI: 10.3390/ijms232012671
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides (LPSs) as Potent Neurotoxic Glycolipids in Alzheimer’s Disease (AD)

Abstract: Lipopolysaccharides (LPSs) are microbiome-derived glycolipids that are among the most potent pro-inflammatory neurotoxins known. In Homo sapiens, the major sources of LPSs are gastrointestinal (GI)-tract-resident facultative anaerobic Gram-negative bacilli, including Bacteroides fragilis and Escherichia coli. LPSs have been abundantly detected in aged human brain by multiple independent research investigators, and an increased abundance of LPSs around and within Alzheimer’s disease (AD)-affected neurons has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 73 publications
(346 reference statements)
0
24
0
Order By: Relevance
“…As such, it was essential to outline the major mechanism whereby LPS triggered in ammation in BREC before we could elucidate if EGCG participated in such pathway. The increased phosphorylation of IκBα and NF-κB p65 along with the translocation of NF-κB p65 to the nucleus in response to LPS con rmed that this molecule works through the canonical NF-κB pathway [39]. Thus, the negative effect of EGCG (in a dose-dependent manner) on the mRNA abundance of TLR4 signaling components, phosphorylation of IκBα, NF-κB p65, NLRP3 and caspase-1 protein abundance con rmed that EGCG elicit an anti-in ammatory response by preventing activation of the NF-κB pathway and NLRP3 in ammasome in ruminal epithelial cells.…”
Section: Discussionmentioning
confidence: 94%
“…As such, it was essential to outline the major mechanism whereby LPS triggered in ammation in BREC before we could elucidate if EGCG participated in such pathway. The increased phosphorylation of IκBα and NF-κB p65 along with the translocation of NF-κB p65 to the nucleus in response to LPS con rmed that this molecule works through the canonical NF-κB pathway [39]. Thus, the negative effect of EGCG (in a dose-dependent manner) on the mRNA abundance of TLR4 signaling components, phosphorylation of IκBα, NF-κB p65, NLRP3 and caspase-1 protein abundance con rmed that EGCG elicit an anti-in ammatory response by preventing activation of the NF-κB pathway and NLRP3 in ammasome in ruminal epithelial cells.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, as a consequence of stroke, the structural integrity of the BBB is affected and under inflammatory conditions, matrix metalloproteinases (MMPs) can degrade basal layer proteins, increasing the BBB’s permeability ( Zlokovic, 2006 ; Lakhan et al, 2013 ). LPS, SCFAs, adiponectin, vasoactive intestinal peptide (VIP), and some neurotransmitter precursors (e.g., 5-HTP) were more readily transported across the BBB to the brain due to increased BBB permeability ( Birdsall, 1998 ; Dogrukol-Ak et al, 2003 ; Nedorubov et al, 2019 ; Megur et al, 2020 ; Formolo et al, 2022 ; Zhao et al, 2022 ).…”
Section: Acupuncture Regulates Intestinal Microbiota In Psdmentioning
confidence: 99%
“…Recently, studies have suggested that dysregulation of the gut microbiome can cause neuroinflammatory disturbances in the CNS that are associated with the progression of neurodegenerative diseases, cognitive impairment, and dementia [73]. Aging, malnutrition, and life in adverse environments can alter the gut microbial profile, which is responsible for increasing the secretion of LPSs and abnormal amyloid proteins aggravating the pathogenesis of Alzheimer's disease (AD) and others [74,75]. The disruption of the blood-brain barrier (BBB) and increased permeability of the compromised gastrointestinal tract facilitate the crossing of LPS and abnormal amyloids that may reach the CNS via the oronasal cavity [76].…”
Section: Effect Of Enteropathy and Gut Dysbiosis On Neurological/cogn...mentioning
confidence: 99%